Presentations for Reforming Agricultural Policies and Farm Support to Advance Sustainable Food System Transformation - Ronchi, Loraine; Ofori, Patrick; Zorya, Sergiy; Fan, Shenggen; Martin, Will (2024)
In the recent COP28 Declaration on Sustainable Agriculture, Resilient Food Systems and Climate Action, world leaders affirmed that “agriculture and food systems must urgently adapt and transform in order to respond to the imperatives of climate change.” This declaration strengthens the growing global consensus that current food systems need urgent transformative change to end hunger and all forms of malnutrition and to make food production and delivery systems resilient and sustainable.